Thermodynamic Performance Analysis of Multi-Effect Distillation for Hypersaline Brine Treatment in Zero Liquid Discharge Applications - Najib Meftah Almukhtar Omar; Bouthyna Faraj Emhemmed Aljamal; Asma Talal Almabrouk Emhemmed; Muhend Milad (African Journal of Advanced Pure and Applied Sciences, 2026)
Water scarcity remains a critical global challenge, exacerbated by climate change and rapid urbanisation, driving an urgent need for robust desalination technologies capable of treating non-conventional feedwaters. This study presents a rigorous thermodynamic evaluation of a four-effect forward-feed Multi-Effect Distillation (MED) system designed for hypersaline brine treatment, a key component in emerging Zero Liquid Discharge (ZLD) frameworks. Using Aspen HYSYS V14.2 with the Electrolyte Non-Random Two-Liquid (NRTL) property package, the system was simulated under elevated feed salinity conditions (NaCl mole fraction 0.03, ≈91,000 ppm), representative of high-recovery Reverse Osmosis (RO) reject streams. The simulation results demonstrate stable operation processing 2,261,000 kg/h of hypersaline feed to produce 564.2 m³/h of high-purity distillate. Despite the significant Boiling Point Elevation (BPE) penalty of 8–10 °C cumulatively, which is approximately 18% higher than standard seawater operations, the system achieved a Recovery Ratio (RR) of 42% and a Gained Output Ratio (GOR) of 4.2. Validation against established literature benchmarks confirmed the model's accuracy within ±12% for Specific Thermal Energy Consumption (STEC). Parametric sensitivity analysis revealed that while freshwater production scales linearly with steam and feed flow rates (R² > 0.98), the thermal duty distribution is heavily influenced by latent heat dominance, with the fourth effect acting as a thermodynamic bottleneck due to increased vapour specific volume at 19 kPa. These findings quantitatively establish the viability of MED as a thermal concentrator for hypersaline brines, bridging the gap between membrane limits and crystallizers to minimise environmental discharge.